Challenges to Bridging Field and Classroom Instruction: Exploring Field Instructors’ Perspectives on Macro Practice - Gita R Mehrotra (2023)
Field education and macro practice have been highlighted as central educational domains in social work education; however, little scholarship has looked at how macro social work practice competencies have been integrated into field-based learning. This exploratory study aimed to gain perspectives from field instructors regarding macro social work and the integration of macro practice into their work with practicum students. Consistent with scholarship that has elucidated the impacts of neoliberalism on social work, including the marginalization of macro practice, emergent themes demonstrated that field instructors face barriers to incorporating macro work into their training of students. Challenges include prevalence of the medical model, time constraints, and funding limitations. Further, field instructors observed gaps among students, their university, and their organizational setting in regard to expectations for integrating macro practice into field education. Recommendations and directions for future research are discussed.